The Brazilian species of the genus Arhacia Herrich- Schäffer, 1855 with description of a new species (Lepidoptera: Notodontidae, Dicranurinae) - V. O. Becker (SHILAP, 2020)
Two species of Arhacia Herrich-Schäffer, 1855 are recorded from Brazil: A. combusta (Herrich-Schäffer, 1854) (= postbrunnea Rothschild, 1917, syn. n.), and A. imitata Becker, sp. n. Images of adults and genitalia are presented.